In patients with anorexia nervosa, myokine levels are altered but are not associated with bone mineral density loss and bone turnover alteration. Issue 5 (10th May 2022) - Maïmoun, Laurent; Mariano-Goulart, Denis; Huguet, Helena; Renard, Eric; Lefebvre, Patrick; Picot, Marie-Christine; Dupuy, Anne-Marie; Cristol, Jean-Paul; Courtet, Philippe; Boudousq, Vincent; Avignon, Antoine; Guillaume, Sébastien; et al.
Abstract : Objectives: The two-fold aim of this study was: (i) to determine the effects of undernutrition on the myokines in patients with restrictive anorexia nervosa (AN) and (ii) to examine the potential link between myokines and bone parameters. Methods: In this study, 42 young women with restrictive AN and 42 age-matched controls (CON) (mean age, 18.5 ± 4.2 years and 18.6 ± 4.2 years, respectively) were enrolled. aBMD and body composition were determined with DXA. Resting energy expenditure (REEm), a marker of energy status, was indirectly assessed by calorimetry. Bone turnover markers and myokines (follistatin, myostatin and irisin) were concomitantly evaluated. Results: AN patients presented low aBMD at all bone sites. REEm, bone formation markers, myostatin and IGF-1 were significantly lower, whereas the bone resorption marker and follistatin were higher in AN compared with controls. No difference was observed between groups for irisin levels. When the whole population was studied, among myokines, only myostatin was positively correlated with aBMD at all bone sites. However, multiple regression analyses showed that in the AN group, the independent variables for aBMD were principally amenorrhoea duration, lean tissue mass (LTM) and procollagen type I N-terminal propeptide (PINP). For CON, the independent variables for aBMD were principally LTM, age and PINP. Whatever the group analysed, none of the myokines appeared as explicative independent variables of aBMD. Conclusion: This study demonstrated that despite the altered myokine levels in patients with AN, their direct effect on aBMD loss and bone turnover alteration seems limited in comparison with other well-known disease-related factors such as oestrogen deprivation.